2020
DOI: 10.1590/1806-9282.66.s2.71
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antihypertensive agents on clinical course and in-hospital mortality: analysis of 169 hypertensive patients hospitalized for COVID-19

Abstract: SUMMARY OBJECTIVE Coronavirus disease 2019 (COVID-19) is an emerging health threat caused by a novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Previous studies have noted hypertension is associated with increased mortality due to COVID-19; however, it is not clear whether the increased risk is due to hypertension itself or antihypertensive agents. We aimed to evaluate the impact of antihypertensive agents on the clinical outcomes of hypertensive patients with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
(4 reference statements)
0
7
0
1
Order By: Relevance
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 95%
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 95%
“…Twenty-seven studies were retrospective, and four studies were prospective observational. Twenty-two studies have already been undergone peer-review [ 9 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. Most studies were conducted in China and Italy.…”
Section: Resultsmentioning
confidence: 99%
“…Whether this influenced the response to COVID-19 remains unknown. CCB treatment, which has antiviral activity [33,34], could be a suitable alternative for some, but not all, conditions for which these agents were prescribed. The benefit-to-harm ratio of continuing to take ACE-I or ARB, which are effective in the treatment and prevention of substantial cardiovascular, diabetic, and renal morbidity and mortality, should be addressed by a comprehensive epidemiological study utilizing reliable available data.…”
Section: Discussionmentioning
confidence: 99%